Nutritional Status and Immune Functions in Maintenance Hemodialysis Patients (Mediators of Inflammation)
Epidemiological studies suggest various kinds of immune dysregulation in hemodialysis (HD) patients. The aim of this study was to investigate the relationship between immune functions and nutritional status of HD patients. We studied 54 patients with ESRD on chronic HD, included 34 females and 20 males with mean age 46.6 ± 16.3 (18–77) years. We measured the height and dry weight of all patients. The BMI was calculated by dividing weight (kg) by height squared ( m 2 ). In all patients serum urea, creatinine, albumin, iron, cholesterol, triglyceride, CRP, IgG, IgM, IgA, CD4, CD8, CD19, CD16-56 lymphocytes were measured. Kt/V values were calculated according to DOQI guideline. In this study, a positive correlation between albumin, cholesterol, and triglyceride levels as nutritional parameters and immune functions in terms of total and subtype lymphocyte counts was observed. Further prospective studies are needed to determine the clinical importance of this finding and the appropriate means of measurement and effects of nutrition on immune function in hemodialysis patients.